Community mitigation of COVID-19: Health communications and varied community reactions. Issue 2 (3rd April 2021) - Meleo-Erwin, Zoë C.; Basch, Corey H.
Abstract: This article introduces a themed issue focused on COVID-19 as it relates to community health. In the context of attempting to curb transmission, a great deal of focus has been placed on community mitigation efforts. These efforts have presented a variety of challenges. This themed issue aims to give an overview of two important aspects of community mitigation, namely, issues relating to COVID-19 related messaging and reactions of different communities to the COVID-19 pandemic. The manuscripts in this issue demonstrate a range of methodology and offer insight into areas of COVID-19 research that can inform community health. They also cover an extensive range of topics and contribute to the literature in terms of informing efforts related to constructing effective messaging and identifying areas of need. Both of these focal points have implications for prevention and intervention.